SISTEM REKOMENDASI ALTERNATIF PRODUK PRO ISRAEL BERBASIS WEBSITE DENGAN METODE CONTENT-BASED FILTERING - Rany Khoirunnissa Putri (Journal of Research and Publication Innovation, 2025)
The genocide committed by Israel against Palestine has raised sympathy from the world community, including Indonesia, by encouraging calls for a boycott of products affiliated with Israel. However, complaints have arisen from the public regarding the boycott due to the difficulty of finding replacement products that are compatible with the affiliated products used. Therefore, a website-based recommendation system for alternative products affiliated with Israel is urgently needed. The recommendation system can help make it easier for people to find alternative products that they want and that match their preferences while the boycott is ongoing. In this study, the recommendation system will be built using the content-based filtering method with TF-IDF and cosine similarity calculations through product type datasets such as brands, categories, and descriptions. This recommendation system generates product recommendations in the top five positions that have the most similarity level to the type of product or keyword that the user inputs into the system with a cosine similarity value of 0.47.